PENGARUH PROSES NETRALISASI PADA SEMI VIRGIN RED PALM OIL DENGAN MENGGUNAKAN NATRIUM HIDROKSIDA (NaOH) TERHADAP KADAR ALB, KADAR KOTORAN DAN KADAR AIR - Mubarokah, Siti; Raja, Pada Mulia; Rahimah; Winardi, Rafael Remit; Fachrizal (Jurnal Agro Fabrica, 2024)
This research aims to determine the effect of the sodium hydroxide (NaOH) neutralization process in semi virgin red palm oil on free fatty acid levels, dirt levels and water content. Efforts to obtain the best quality red palm oil can be done by administering sodium hydroxide (NaOH). The method used in this research was a non-factorial Completely Randomized Design (CRD) using the chemical Sodium Hydroxide (NaOH) with concentrations of 3%, 4% and 5% of the sample weight. Each chemical and its concentration was repeated in 3 repetition units. The types of observations carried out are ALB levels, dirt levels, water content. The data obtained were analyzed using the Anova Test and Duncan's Test. The research results show that sodium hydroxide (NaOH) can reduce ALB levels by up to 0.13%. In the Dirt Content parameter, the chemical sodium hydroxide (NaOH) can reduce the dirt content by 0.0024% and in the Water Content parameter, the use of the chemical sodium hydroxide (NaOH) can reduce the water content by up to 0.0027%. With the conclusion that the use of the chemical resist sodium hydroxide as an efficient catalyst in the SVCPO neutralization process.